Índice de protección hidrológica en relación a la flora arbórea y valoración de suelo de la microcuenca Membrillo, cantón Bolívar- Manabí - Cabezas Cacierra, Josselin Dennis (2021)
This research aimed to evaluate the relationship of the arboreal flora with the protection of the soil in the Membrillo micro-basin, Bolívar canton, Manabí province. For this, cartographic information from MAG (Ministry of Agriculture and Livestock) and data obtained from visits to the Membrillo micro-basin were used. To determine the vegetation cover in the Membrillo micro-basin, 28 sampling points were selected, while for the calculation of HPI the methodology of (Romero and Ferreira, 2010) was used, which consisted of carrying out radiated transects, with a radius of 50 m, in order to observe the vegetation cover every 0.5 m. 7 indicators were used (structure, density, interception of precipitation, presence of mulch, special characteristics, type of vegetation and degree of intervention). According to the calculation carried out, it was determined that in the micro-basin there are 5 types of plant cover, among which are: 50% fruit trees / 50% cultivated grass; 70% tropical arboriculture / 30% cultivated grass; 70% cultivated grass / 30% fruit trees, 100% tropical arboriculture and 100% natural forest. The one that provides the greatest hydrological protection is the natural forest with 1. While the protection index The hydrological level of the Membrillo micro-basin is 0,68 ≅ 0,7 determining it as an area of medium protection, due to its moderately good condition, of medium importance, with an aptitude for conservation, concluding that it is necessary to propose conservation and / or repair alternatives for the Membrillo micro-basin which has a surface area of 116.69 km2, the proposed alternatives mostly contemplate the sowing of plant species (arboreal, shrub, herbaceous) and the application of organic fertilizers and fertilizers.